2016
DOI: 10.1111/jofi.12371
|View full text |Cite
|
Sign up to set email alerts
|

Trade Credit and Industry Dynamics: Evidence from Trucking Firms

Abstract: Long payment terms are a strong impediment to the entry and survival of liquidity constrained firms. To test this idea and its implications, I consider the effect of a reform restricting the trade credit supply of French trucking firms. In a difference-in-differences setting, I find that trucking firms' corporate default probability drops by one-fourth following the restriction. The effect is persistent, concentrated among liquidity constrained firms, and not offset by a drop in profits. The restriction also t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
129
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(146 citation statements)
references
References 96 publications
4
129
0
1
Order By: Relevance
“…In order to avoid a bad control problem, we measure bank-level controls as of December 31, 1982 (prior to the announcement of the relocation) and interact each with our P ost t dummy (Barrot (2016) Including these covariates to capture economic conditions and bank characteristics is intended to mitigate possible biases that may occur if these variables affect Y i,t and are correlated with P ost t × T reatment i , but not considered in the estimation. Finally, we include a full complement of bank and time fixed effects, denoted ψ i and η t , respectively.…”
Section: Empirical Methodologymentioning
confidence: 99%
“…In order to avoid a bad control problem, we measure bank-level controls as of December 31, 1982 (prior to the announcement of the relocation) and interact each with our P ost t dummy (Barrot (2016) Including these covariates to capture economic conditions and bank characteristics is intended to mitigate possible biases that may occur if these variables affect Y i,t and are correlated with P ost t × T reatment i , but not considered in the estimation. Finally, we include a full complement of bank and time fixed effects, denoted ψ i and η t , respectively.…”
Section: Empirical Methodologymentioning
confidence: 99%
“…3 Trade credit claims, recorded as accounts receivable on firms' balance sheets, are typically seen as short-term, liquid, low-risk claims that should be very easy to pledge, and that should not constrain firm growth. Yet recent research as found that long payment terms forces financially constrained firms to cut back investment (Murfin and Njoroge 2014) and exposes them to liquidity risk (Barrot 2015). 4 Our work shows that trade 2 The effect of financing frictions on capital investment has been studied extensively, starting with Fazzari et al (1988), who find a strong positive relationship between cash flows and investment.…”
mentioning
confidence: 88%
“…While economics and finance literature offers a variety of theoretical justifications and rich empirical evidence for the use of trade credit (see Smith 1987, Lee and Stowe 1993, Long et al 1993, Petersen and Rajan 1997, Biais and Gollier 1997, Giannetti et al 2011, Klapper et al 2012, Barrot 2016, OM researchers offer new insights by modelling detailed and strategic interactions of the firms in the supply chain. OM research in trade credit has a long history, from early works by Baranek (1967) and Haley and Higgins (1973) to recent papers by Gupta and Wang (2009) and Babich and Tang (2012) (for quick references to work in this area, see Babich et al 2012, Kouvelis andZhao 2012).…”
Section: Supply Chain Financementioning
confidence: 99%